Egalitarian religion and economics - Carmel Ullman Chiswick (Institute for the Study of Labor (IZA), 2010)
The role of women in the ritual of many religions changed dramatically at the end of the 20th century, to the point where full participation by women was the norm by 2000 rather than the rarity that it had been 30 years earlier. This paper considers some aspects of the economic context that help explain why the movement toward egalitarianism succeeded in that period in contrast to its many previous failures. It concludes with predictions of future trends.
Keywords: J16; Z12; J13; 330; Economics; gender; religion; fertility; Religion; Geschlecht; Gleichberechtigung; Familienökonomik; Fruchtbarkeit; USA